KECENDERUNGAN PELANGGARAN PERJANJIAN UTANG PADA PERUSAHAAN KONSTRUKSI DAN PROPERTI DI BEI - Billy Dermawan; Yunia Panjaitan (Universitas Katolik Indonesia Atma Jaya, 2020)
The importance of debt covenant violation is to minimize the debtholder default risk. The possibility of debtholder’s default risk may be caused by liquidity problems, low profitability, and bad quality of earnings. Hence, this study aims to proof the tendency of debtholder to violate debt covenants by measuring current ratio volatility, return on assets, and earnings quality as independent variables. By using five companies from construction and property sub-sector that listed on Indonesia Stocks Exchange in 2016- 2018, the data are analyzed with multiple linear regression model for panel data. From this study, we can conclude that the impact of return on assets to debt covenant violation is significantly negative, debtholders with poor financial performance have higher potential to do debt covenant violation. However, there is no evidence that debt covenant violation is affected current ratio volatility and earnings quality.